GAMPONG GOVERNMENT ADMINISTRATION SYSTEM FOR THE COMMUNITY IN SIGLI CITY DISTRICT - Zulfikar; Rozaili; Mulyadi (FISIP Universitas Malikussaleh, 2026)
This study aims to determine the extent to which the village government's administrative service system in Kota Sigli District, Pidie Regency, meets community needs. Quality administrative services are a key indicator in assessing the effectiveness of government administration at the lowest level, therefore, a study is needed to examine how services are implemented, the obstacles that arise, and possible improvements. This study used a descriptive method with a qualitative approach, using field research and literature review to obtain relevant data.The results indicate that administrative services in several villages are not yet optimal. The main obstacles identified include low levels of education and skills among village officials, a lack of understanding of administrative tasks, and limited facilities and infrastructure such as computers, stationery, and other supporting facilities. This situation impacts the slow service process and the failure to meet community service standards. Improvements can be made through increasing the capacity of village officials by considering educational qualifications in the selection process, providing administrative training, and providing adequate work facilities. Furthermore, the optimal utilization of village head offices needs to be strengthened so that administrative services can be more effective, focused, and sustainable, supporting better village governance. The results indicate that administrative services in several villages are not yet optimal. The main obstacles identified include low levels of education and skills among village officials, a lack of understanding of administrative tasks, and limited facilities and infrastructure such as computers, stationery, and other supporting facilities. This situation impacts the slow service process and the failure to meet community service standards. Improvements can be made through increasing the capacity of village officials by considering educational qualifications in the selection process, providing administrative training, and providing adequate work facilities. Furthermore, the optimal utilization of village head offices needs to be strengthened so that administrative services can be more effective, focused, and sustainable, supporting better village governance.